(1→6)-β-d-Glucan as Cell Wall Receptor for Pichia membranifaciens Killer Toxin - Santos, A. (American Society for Microbiology, 2000)
The killer toxin from Pichia membranifaciens CYC 1106, a yeast isolated from fermenting olive brines, binds primarily to the (1→6)-β-d-glucan of the cell wall of a sensitive yeast (Candida boidinii IGC 3430). The (1→6)-β-d-glucan was purified from cell walls of C. boidinii by alkali and hot-acetic acid extraction, a procedure which solubilizes glucans. The major fraction of receptor activity remained with the alkali-insoluble (1→6)-β- and (1→3)-β-d-glucans. The chemical (gas-liquid chromatography) and structural (periodate oxidation, infrared spectroscopy, and (1)H nuclear magnetic resonance) analyses of the fractions obtained showed that (1→6)-β-d-glucan was a receptor. Adsorption of most of the killer toxin to the (1→6)-β-d-glucan was complete within 2 min. Killer toxin adsorption to the linear (1→6)-β-d-glucan, pustulan, and a glucan from Penicillium allahabadense was observed. Other polysaccharides with different linkages failed to bind the killer toxin. The specificity of the killer toxin for its primary receptor provides an effective means to purify the killer toxin, which may have industrial applications for fermentations in which salt is present as an adjunct, such as olive brines. This toxin shows its maximum killer activity in the presence of NaCl. This report is the first to identify the (1→6)-β-d-glucan as a receptor for this novel toxin.